2020
DOI: 10.3390/cancers12061397
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Functionalized Magnetic Nanoparticles to Target Breast Cancer Cells Including Cancer Stem-Like Cells

Abstract: Nanotechnology-based approaches hold substantial potential to avoid chemoresistance and minimize side effects. In this work, we have used biocompatible iron oxide magnetic nanoparticles (MNPs) called MF66 and functionalized with the antineoplastic drug doxorubicin (DOX) against MDA-MB-231 cells. Electrostatically functionalized MNPs showed effective uptake and DOX linked to MNPs was more efficiently retained inside the cells than free DOX, leading to cell inactivation by mitotic catastrophe, senescence and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Hence, our proposed nanocarrier offers a potential solution to avoid the toxicity and the lack of effectiveness of gemcitabine in its clinical use [3,4] and it is expected to remain intact in blood circulation [50]. The stability and efficacy of disulfidebased drug delivery systems have been widely studied, showing promising results in breast cancer [51], uveal melanoma [52], and pancreatic cancer models [19], among others.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our proposed nanocarrier offers a potential solution to avoid the toxicity and the lack of effectiveness of gemcitabine in its clinical use [3,4] and it is expected to remain intact in blood circulation [50]. The stability and efficacy of disulfidebased drug delivery systems have been widely studied, showing promising results in breast cancer [51], uveal melanoma [52], and pancreatic cancer models [19], among others.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no previous reports have investigated the influence of anticancer drugs conjugated with QDs on the induction of cellular senescence. Further, only a few studies have shown the influence of drugs (e.g., doxorubicin; DOX) conjugated with other NPs on the induction of senescence [ 37 ]. Lazaro-Carrillo A. et al showed that iron oxide magnetic NPs (MF66) alone did not induce senescence in MDA-MB-231 cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cell cycle of photodynamic treated cells grown in F25 flasks was evaluated at different post-irradiation times (12, 24, and 72 h), as previously described [ 77 ].…”
Section: Methodsmentioning
confidence: 99%